2023
DOI: 10.1108/apjml-11-2022-0945
|View full text |Cite
|
Sign up to set email alerts
|

The perceived value of digital fashion product and purchase intention: the mediating role of the flow experience in metaverse platforms

Abstract: PurposeThis paper aims to explore digital fashion products in the metaverse platform contexts and empirically examine the effect of the metaverse platform characteristics on the purchase intention of digital fashion products through users' flow experience and perceived value of the products.Design/methodology/approachA survey method was used in this study. Answers from 314 metaverse users were analyzed, and the hypotheses were tested using the structural equations modeling and bootstrapping analysis.FindingsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…When Ma & Chen (2023) and Park et al (2023) analyzed consumers' purchase intention, they found that when the external environment affects consumers' purchase intention, perceived value will act as a mediating response.…”
Section: Customer Experience and Purchase Intentionmentioning
confidence: 99%
“…When Ma & Chen (2023) and Park et al (2023) analyzed consumers' purchase intention, they found that when the external environment affects consumers' purchase intention, perceived value will act as a mediating response.…”
Section: Customer Experience and Purchase Intentionmentioning
confidence: 99%
“…Metaverse has the potential to drastically alter the user experience and empower consumers (Wongkitrungrueng & Suprawan, 2023). Factors such as vividness, telepresence, interactivity, informativeness and flow enhance the user experience in the metaverse (Barta et al, 2023; Haikel‐Elsabeh, 2023; Kim, 2021; Park et al, 2023; Patil & Pramod, 2023). The feeling of presence and realism are also widely agreed‐upon attributes of the metaverse (Kim et al, 2023; Oh et al, 2023; Zhang et al, 2022).…”
Section: Metaverse: Concept and Componentsmentioning
confidence: 99%